Awards Bring Hope and Cheer - Sunday Star, Tan Ee Loo (2008)
Rachel Sivanathan tires the knot at the age of 20 - it was an arranged marriage. she looked forward to continuing her studies but that plan had to be put on hold with the arrival of her first-born the following year.